Mutational Analysis of TCOF1, GSC, and HOXA2 in Patients With Treacher Collins Syndrome - Hao, Shaojuan (J Craniofac Surg, 2016)
Treacher Collins syndrome is an autosomal dominant craniofacial malformation mainly caused by mutations in the TCOF1 gene. Few cases have been observed in the Chinese population. Herein, the authors report the mutational analysis of TCOF1, GSC, and HOXA2 to determine the mutational features of the 3 genes in Chinese patients with Treacher Collins syndrome. Genomic DNA of the patients and their parents was extracted from peripheral blood following a standard protocol. DNA sequencing analysis was performed on all exons and the exon-intron borders of TCOF1, GSC, and HOXA2 in addition to the 1200-bp upstream of TCOF1. Four novel single nucleotide polymorphisms were detected in TCOF1, one of which was in the promoter region. Mutations in GSC and HOXA2 were not found in the 3 patients. Our results suggest the possibility of genetic heterogeneity or different mechanisms leading to the disease. Further functional study of the alteration is necessary to obtain more definitive information.